“Calentando los huesos de las tumbas”. El cuerpo post-orgiástico y el ocaso del mundo mediterráneo en “Makbara” de Juan Goytisolo - Łukaszyk, Ewa (Studia Romanica Posnaniensia, 2013)
The key issue of the analysis, concentrated on the dystopia by Juan Goytisolo, Makbara, is the condition of human sexual body which, in terms proposed by Baudrillard, can be qualified as post-orgiastic. While an asexual, aseptic social system is created in the modern, civilized Europe, Morocco seems to be the last refuge not only for the marginalized sexuality, but also for the romantic dreams about marriage. Nonetheless, the Moroccan promise of authentic eroticism acquires a necrophilic flavour of “love at the cemetery”. In the conclusion, Goytisolo is shown as the advocate of a dying, spectral culture, victim of unceasing, manifold exploitation and unable to counterbalance the European symbolic and economic predominance in the Mediterranean.